Deep Randomized Distributed Function Computation (DeepRDFC): Neural Distributed Channel Simulation - Bergstrom, Didrik; Gunlu, Onur (Proceedings / IEEE International Symposium on Information Theory, 2025)
The randomized distributed function computation (RDFC) framework, which unifies many cutting-edge distributed computation and learning applications, is considered. An autoencoder (AE) architecture is proposed to minimize the total variation distance between the probability distribution simulated by the AE outputs and an unknown target distribution, using only data samples. We illustrate significantly high RDFC performance with communication load gains from our AEs compared to data compression methods. Our designs establish deep learning-based RDFC methods and aim to facilitate the use of RDFC methods, especially when the amount of common randomness is limited and strong function computation guarantees are required.